Green Building Performance Assessment with EDGE Building App on Clinic Design Implementing Passive Design Strategy from Climate Consultant - Yudha Kusuma; Fritz Akhmad Nuzir; Ai Siti Munawaroh (JURNAL ARSITEKTUR, 2022)
Carbon emissions contributed by the construction sector currently have a major impact on environmental climate change. In the construction sector, the solutions offered in mitigating the impacts of climate change include developing sustainable building designs in terms of energy efficiency. The design approach with building performance simulation could ensure the application of environmentally friendly principles in the design process. The research methodology utilized a building performance simulation method using the Climate Consultant application in presenting a summary of climate data on the site and generating recommendations for passive design strategies. After the application of these recommendations to the design of the clinic, then an evaluation of the performance of the building was carried out using the EDGE Building App. From building performance simulations carried out in study case examples using the Climate Consultant application, recommendations were obtained in the form of 20 passive design strategies in which ten strategies could be applied. The design results obtained are proven to have an arguably good energy efficiency when evaluated with the EDGE Building App. This evaluation also provided recommendations for several reduction and saving steps from three aspects of building elements, namely: energy consumption (28.53%), water use consumption (20.77%), and types of building materials (84.02%).